(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Rapid advancement of biomedical knowledge along with consistent increase in technical facilities in medical science changes the teaching-learning processes of undergraduate medical course in many countries and Anatomy is no exception. Some of these changes have been incorporated into the undergraduate medical course in Bangladesh and some are yet to be incorporated. In this situation, a thorough understanding is required to know how different aspects of Anatomy are distributed in terms of weightage in the written assessment of Anatomy course, which indirectly influence the learning of the course. To have an insight regarding this, thorough analyses of recent question papers of two universities were done in this study. Objectives: Analyses of question papers give a clue about the variation in the distribution of weightage in different aspects of Anatomy in the undergraduate written exams (due to absence) in terms of allocation of proper weightage in the curriculum. Study design: A descriptive, observational study involving quantitative analysis. Place and period of study: Anatomy Department of AFMC from March 2012 to August 2012. Materials and Methods: The study includes analysis of 28 short answer question papers and 23 multiple choice question papers of two universities in Dhaka. This is a quantitative study and means of percentage value were calculated by using SPSS program for analyzing the question paper. Results: It is observed from the analyses that Topographic Anatomy got maximum coverage (40-89%) and aspects like Genetics, Radiographic Anatomy and Surface was covered less than 3% (absent in some question papers) of the question papers. The result of the present study will help in improvement of present written assessment system of the undergraduate Anatomy course. Conclusion: From result and analysis it is evident that the present assessment system needs to give proper weightage to different aspects of Anatomy to make the assessment more valid, objective and reliable. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18729 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 75-83